(untitled) (Modern information system and technologies, 2018)
The globalization of information resources has led to the return to the concept of large data centers that provide cloud computing services. The reduction of energy costs from the operation of such centers has become a problem of international scale. Planning an energy efficient cloud infrastructure requires modeling its operation to verify compliance with service quality requirements.